Algorithm for construction of LMI-domains of stability of modal control - Sych, Maryna; Goncharenko, Boris (My University, 2018)
The solution of the problem of constructing modal regulators for linear multidimensional systems providing D-stability (asymptotic stability) of the control object is given. The described methods for solving the problem not only of direct modal control, but other tasks modal regulations, which demand precise placing the roots in the left half-plane complex is not applied, and only need their belonging to given areas.
Keywords: modal control; regulators; Luenberger observers; D-stability; linear matrix inequalities; matrix kronecker product; модальне керування; регулятори; D-стійкість; спостерігачі Луенбергера; лінійні матричні нерівності; кронекеровий добуток матриць; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка